2005
DOI: 10.1086/430774
|View full text |Cite
|
Sign up to set email alerts
|

Observational Evidence of the Formation of Cyanopolyynes in CRL 618 through the Polymerization of HCN

Abstract: The abundance ratio of consecutive members of the cyanopolyynes family has been explored in CRL618 using data acquired in a complete line survey covering the frequency range 81-356 GHz. The J up range explored for the different molecules is the following: 1 to 4 for HCN and HNC, 9 to 39 for HC 3 N, 31 to 133 for HC 5 N, and 72 to 85 for HC 7 N (not detected beyond J up =85). The lowest vibrationally excited state of HC 7 N (ν 15 at 62 cm −1 ) has been tentatively detected. Data analysis has been performed by e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 16 publications
2
33
0
Order By: Relevance
“…23, 26, 27, and 47). In CRL 618, the chemistry is dramatically altered by UV radiation, indicated by appearance of ions (HCO ϩ ) and an enhancement of the cyanopolyyne chains (48). These PPN are the only other sources of metal-containing species, with the exception of one O-rich star (see below).…”
Section: Distinctmentioning
confidence: 99%
“…23, 26, 27, and 47). In CRL 618, the chemistry is dramatically altered by UV radiation, indicated by appearance of ions (HCO ϩ ) and an enhancement of the cyanopolyyne chains (48). These PPN are the only other sources of metal-containing species, with the exception of one O-rich star (see below).…”
Section: Distinctmentioning
confidence: 99%
“…HC 3 N HC 3 N is commonly observed in AGB stars and proto-PNs (e.g., Cernicharo et al 2000;Pardo et al 2004). Pardo et al (2005) found that HC 3 N is quickly reprocessed from HCN in PPN stage. Prior to this work, HC 3 N has never been detected in PNs and its absence is often explained as the result of efficient photodissociation due to the strong UV radiation in PNs.…”
Section: Hncmentioning
confidence: 99%
“…See e.g. Cernicharo et al (2001), Cernicharo (2004), Pardo et al (2005) and references therein; there is also a very interesting poster in this symposium on this source (Pardo et al). Models explain the presence of all these molecules assuming photoinduced chemistry.…”
Section: Chemical Evolution In Pnementioning
confidence: 98%